SOSIALISASI PENGGUNAAN APLIKASI “SIMOTOR” UNTUK PENJUALAN SPAREPART DI BENGKEL FAKHRY MOTOR - Muhammad Sendi Prasetyo; Wahyu Eko Pujianto (Pastabiq : Jurnal Pengabdian Kepada Masyarakat, 2023)
The Fakhry Motor Workshop has the opportunity to develop sales of spare parts at the Fakhry Motor Workshop using the "Simotor. This service aims to socialize the use of the "Simotor" application to local people who want to buy motorbike spare parts. The method of community service activities uses the qualitative method through the process of observation, interviews and documentation. The informants involved in the information gathering process were the owners and mechanics of the Fakhry Motor workshop. The results of this community service activity show that the use of the "Simotor" application can be understood by the owner and mechanic of the Fakhry Motor workshop. The "Simotor" application can be used for the process of buying and selling motorbike spare parts. The use of the "Simotor" application can be aimed at people who are lazy to leave the house. The "Simotor" application can be sent via courier such as in the online sales market. The "Simotor" application payment system can be via transfer or cod.